The Role of Loan Loss Provisions in Earnings Management and Capital Management: The Chinese Experience - REN, JINGYI (2018)
Banks’ loan loss provisions play an important role in bank stability and soundness. It can help banks prevent credit risk, smooth income, manage regulatory capital and also improve their performance. This paper examines the loan loss provisions behaviours in Chinese banking system and how they are correlated with the earnings management and capital management. Based on 260 banks over the period of 2011-2017, both the Fixed Effects model and the System Generalized Method of Moments estimator are used to assist our analysis.